Risk of bloodborne pathogen exposure among Zambian healthcare workers - Elayne Kornblatt Phillips; Owen J. Simwale; Matthew J. Chung; Ginger Parker; Jane Perry; Janine C. Jagger (Elsevier, 2012)
Purpose: Understanding the risks of bloodborne pathogen transmission is fundamental to prioritizing interventions when resources are limited. This study investigated the risks to healthcare workers in Zambia. Design: A survey was completed anonymously by a convenience sample of workers in three hospitals and two clinics in Zambia. Respondents provided information regarding job category, injuries with contaminated sharps, hepatitis B vaccination status and the availability of HIV post-exposure prophylaxis (PEP). Results: Nurses reported the largest number of injuries. The average annual sharps injury rate was 1.3 injuries per worker, and service workers (housekeepers, laundry, ward assistants) had the highest rate of these injuries, 1.9 per year. Injuries were often related to inadequate disposal methods. Syringe needles accounted for the largest proportion of injuries (60%), and 15% of these injuries were related to procedures with a higher-than-average risk for infection. Most workers (88%) reported the availability of PEP, and only 8% were fully vaccinated against hepatitis B. Conclusions: The injury risks identified among Zambian workers are serious and are exacerbated by the high prevalence of bloodborne pathogens in the population. This suggests that there is a high risk of occupationally acquired bloodborne pathogen infection. The findings also highlight the need for a hepatitis B vaccination program focused on healthcare workers. The risks associated with bloodborne pathogens threaten to further diminish an already scarce resource in Zambia - trained healthcare workers. To decrease these risks, we suggest the use of low-cost disposal alternatives, the implementation of cost-sensitive protective strategies and the re-allocation of some treatment resources to primary prevention. Keywords: Healthcare worker safety, Zambian healthcare workers, Bloodborne pathogen transmission, Sharps injury prevention, Infectious diseases